1989
DOI: 10.1530/jrf.0.0860723
|View full text |Cite
|
Sign up to set email alerts
|

Human oocyte-cumulus complexes stimulate the human acrosome reaction

Abstract: Oocyte-cumulus complexes were obtained, after induced ovulation, from infertile patients participating in an in-vitro fertilization programme. About 6 h after retrieval and depending on the expansion of the cumulus, 100,000 motile spermatozoa, prepared by a migration-centrifugation method, were added. After 14-18 h incubation at 37 degrees C, oocytes were examined for signs of fertilization (pronuclei and polar body formation) and then removed; spermatozoa remaining in the incubation medium were fixed for tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…Additionally, the viscoelastic properties of the cumulus mass apparently aid in protecting the oocyte from the mechanical stress produced by the process of extrusion. The results of these and other studies support the possibility that the presence of an intact and successfully expanded cumulus mass aids in oocyte maturation, optimal ovulation and fertilizability [26], oocyte transport to the oviduct [33], the zona reaction [34], sperm motility [35][36][37], sperm attraction [38], sperm selection [39,40], and the acrosome reaction [41].…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Additionally, the viscoelastic properties of the cumulus mass apparently aid in protecting the oocyte from the mechanical stress produced by the process of extrusion. The results of these and other studies support the possibility that the presence of an intact and successfully expanded cumulus mass aids in oocyte maturation, optimal ovulation and fertilizability [26], oocyte transport to the oviduct [33], the zona reaction [34], sperm motility [35][36][37], sperm attraction [38], sperm selection [39,40], and the acrosome reaction [41].…”
Section: Introductionsupporting
confidence: 57%
“…It has been established here and in previous studies that an intact cumulus mass protects developing oocytes before and after fertilization [25,26,[33][34][35][36][37][38][39][40][41]. For example, Sato et al [48] demonstrated that cumulus-produced component(s) (i.e., glycosaminoglycans) delay the degenerative process during in vitro oocyte culturing.…”
Section: Disruption Of Cumulus Expansion Affects the Development Of Cmentioning
confidence: 73%
“…Another unresolved question concerns the real inducer(s) of the AR in fertilizing spermatozoa in vivo. Although the cumulus oophorus surrounding oocytes has been implicated as the site of the AR in some mammalian species such as human (Stock et al , 1989) and shrew (Kaneko et al , 2001) there is no unequivocal evidence to support this view in mouse. In a previous work from our group using in vitro fertilization (IVF), we observed that the AR, as shown by a loss of EGFP fluorescence in the acrosome, rarely begins while spermatozoa are traveling through the cumulus (Hirohashi et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the zona pellucida (Cross et al, 1988) and cumulus oophorus (Siiteri et al, 1988a;Stock et al, 1989), various components of follicular fluid from several mammalian species have been discussed as possible initiators of the AR in vitro (Meizel, 1985).…”
Section: Introductionmentioning
confidence: 99%